Design of "VERB-ING FOR FUN" Learning Media For Student 4th Class Primary School : Perancangan Media Pembelajaran "VERB-ING FOR FUN" Untuk Siswa Kelas 4 Sekolah Dasar - -, Raka Arya Pratama; Armin, Aidil Primasetya (JOINCS (Journal of Informatics, Network, and Computer Science), 2024)
Abstract. MI Al-Ihsan Sidoarjo is a madrasa school located in Sidoarjo, East Java. However, the teachers there still rely on textbooks and question sheets for their teaching methods, and do not have projectors to use PowerPoint as another teaching method, which often causes students to not understand the essence of the lessons being delivered, due to the detailed delivery of the material. With these considerations in mind, the researcher solved the problem at MI Al-Ihsan by creating an interactive learning media application called "Verb-ng for Fun" specifically for English lessons which can be accessed using a computer in the lab, so that it can be used by MI English teachers. Al-Ihsan as a supporter for delivering lesson material. In designing it, the researcher studied the English teacher at MI Al-Ihsan and used the material in the textbook as application design material. The researcher aims to use the ADDIE method as a reference for designing interactive learning media applications that will be created. It is hoped that the design of this application can be used to improve students' understanding of English lessons.